Facilitating mental health help-seeking by young adults with a dedicated online program: a feasibility study of Link. Issue 7 (9th July 2017) - Kauer, Sylvia D; Buhagiar, Kerrie; Blake, Victoria; Cotton, Sue; Sanci, Lena
Abstract : Objective: To explore the feasibility of a dedicated online youth mental health help-seeking intervention and to evaluate using a randomised controlled trial (RCT) study design in order to identify any modifications needed before commencement of the full-scale RCT. Design: A pilot RCT with 1:1 randomisation to either the intervention or comparison arm. Setting: An online study conducted Australia-wide. Participants: 18–25 year olds living in Australia were recruited via social media. Intervention: Link is a dedicated online mental health help-seeking navigation tool that matches user's mental health issues, severity and service-type preferences (online, phone and face-to-face) with appropriate youth-friendly services. The comparison arm was usual help-seeking strategies with a link to Google.com. Main outcome measures: The primary outcome was the number of acceptability and feasibility criteria successfully met. Intervention and study design acceptability and feasibility were assessed by nine criteria. Secondary outcomes, via online surveys (at baseline, 1 week and 1 month) measured service use, help-seeking intentions, psychological distress, barriers to help-seeking, attitudes towards mental health help-seeking, mental health literacy, satisfaction and trust. Results: Fifty-one participants were randomised (intervention: n=24; comparison: n=27). Three out of four of the intervention and two out of five of the study design criteria were met. Unmet criteria could be addressed by modifications to the study design. Qualitative analysis demonstrated that Link was useful to participants and may have increased their positive experiences towards help-seeking. There were no observable differences between arms in any outcome measures and no harms were detected. Conclusion: Generally, the Link intervention and study design were acceptable and feasible with modifications suggested for the four out of nine unmet criteria. The main trial will hence have shorter surveys and a simpler recruitment process, use positive affect as the primary outcome and will not link to Google.com for the comparison arm. Trial registration number: Australian New Zealand Clinical Trials Registry, ACTRN12614000386639.